The Comparison Of Cooling Load Calculation Using Manual Method And Hourly Analysis Program - Saragasan, Sunder; sies, mohamad farid (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Achieving a efficient system of air conditioning is required to both maximize the thermal comfort and the overall energy consumption and etermining the cooling load through calculation helps this. The primary objective of this research is determine and compare the cooling load using Hourly Analysis program to manual method such as CLTD method of FPTV (Block C&D), UTHM. Measurements from floor plan and prior study of CLTD cooling load calculation method were used to determine the cooling load in HAP software. The cooling load calculation by the HAP software is 3,275,100 BTU/hr (272.9 RT) is 77.9% efficient to chiller capacity and there is 5.79% difference compared to CLTD method. The research can be extended o non-air conditioned spaces in HAP software for future researches.